Geographic Information System for Land Suitability Mapping of Partner Farmers at Okiagaru Indonesia Agricoop Using Rule-Based System and Prototype Methodology - Wicaksono, Aditya; Manalu, Doni Sahat Tua; Sebayang, Veralianta Br; Pratama, Agief Julio; Pamungkas, Muhammad Aldryansyah; Puspa, Amelia Setya (Informatika, Universitas Jenderal Soedirman, 2026)
Geographic Information System (GIS) for land suitability assessment integrates spatial and attribute data to evaluate and map areas for food crops and horticulture. The system applies parameters such as temperature, rainfall, water pH, clay CEC, organic carbon, and other soil characteristics, analyzed through a rule-based approach. Its main goal is to optimize agricultural land use by aligning crop selection with physical and environmental conditions. GIS-based analysis enables accurate digital mapping and categorizes land into highly suitable, moderately suitable, marginally suitable, and unsuitable classes, providing valuable insights for farmers, governments, and stakeholders in sustainable land management. System development employed the Prototype methodology, emphasizing iterative stages of requirement gathering, rapid design, prototype construction, user evaluation, and refinement. The Land Suitability GIS (SigKL) was tested at five partner-farmer sites in Cianjur and Sukabumi. Black Box Testing confirmed that all 20 functional features achieved a 100% success rate. The system supports the identification of potential new agricultural areas and offers recommendations for improving less productive land. The novelty of this research lies in integrating FAO (1976) classification with interactive digital mapping and locally tailored knowledge rules, enabling real-time accessibility. Unlike prior studies limited to static analysis, SigKL introduces an adaptive, rule-based GIS prototype with interactive visualization, directly supporting decision-making for sustainable agriculture. This innovation enhances transparency and accessibility, contributing to the Sustainable Development Goals (SDGs) related to food security and sustainable farming.